A lead-free environment-friendly sodium bismuth titanate-based composite dielectric energy storage ceramic prepared by a rapid sintering technique, and a preparation method and application thereof
Patent Information
- Application Number
- CN202410662972.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-05-27
AI Technical Summary
[0031]本发明提供的一种快速烧结技术制备的具有优异介电温度稳定性的无铅环保钛酸铋钠基复合介质储能陶瓷的应用,用于陶瓷储能电容器,兼具优异介电温度稳定性及储能特性。
Smart Images

Figure CN118545994B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of X9R temperature-stable high-pulse-power ceramic capacitor technology, specifically to a lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability prepared by rapid sintering technology, its preparation method, and its application. Background Technology
[0002] In recent years, the rapid development of electronic devices and power systems has led to an increasing demand for energy storage materials that simultaneously possess a wide operating temperature range and high power density. Furthermore, due to the escalating problems of air pollution and climate change, researchers are actively seeking new environmentally friendly energy storage materials.
[0003] Compared to chemical batteries and electrochemical capacitors, dielectric energy storage capacitors offer advantages such as high power density, short charge / discharge times, and high cycle reliability. Among the many dielectric energy storage capacitor materials, bulk ceramic capacitors have attracted widespread attention due to their relatively high dielectric constant, moderate breakdown field strength, excellent thermal stability, superior mechanical strength, and low cost.
[0004] With the rapid development of technology, novel rapid sintering technologies have been used in the past few decades for the high-throughput preparation of advanced ceramic materials. Among them, spark plasma sintering (SPS) has become an advanced sintering technology, mainly because, compared with conventional processes, it can sinter various materials to full density at lower homogenous temperatures and in shorter durations while maintaining grain size. These advantages, compared with external heating in conventional sintering, are largely attributed to the localized internal heating mechanism in SPS.
[0005] The preparation of high-throughput ceramic materials with excellent electrical properties and excellent dielectric temperature stability using SPS sintering technology has become a current research hotspot. Summary of the Invention
[0006] The purpose of this invention is to provide a lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability, prepared by a rapid sintering technology, and its preparation method. The rapid sintering technology for preparing this ceramic offers advantages such as fast sintering speed, high reliability, and low raw material cost, making it suitable for widespread application. Furthermore, it is environmentally friendly and meets environmental protection requirements. The resulting bulk ceramic capacitor material combines excellent dielectric temperature stability and energy storage characteristics, exhibiting high throughput and good repeatability, and has promising prospects for industrialization.
[0007] The specific technical solution of this invention is as follows:
[0008] A lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability, prepared by rapid sintering technology, is (100-xy) mol% Na 0.5 Bi 0.5 TiO3- x mol% K 0.5 Bi 0.5 TiO3- y mol% Sr 0.2 5Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 O3- z wt% MeF2, 18 < x < 22.9, 5.9 < y < 9.5, 4.6 < z < 6.7, Me = Ca, Sr or Ba (any one);
[0009] This invention provides a method for preparing a lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability using a rapid sintering technology, comprising the following steps:
[0010] 1) Using any one of the following as starting materials: titanium dioxide, bismuth trioxide, anhydrous potassium carbonate, anhydrous sodium carbonate, tin dioxide, zirconium dioxide, calcium carbonate, strontium carbonate, calcium fluoride, strontium fluoride, and barium fluoride, according to (100-xy)mol% Na 0.5 Bi 0.5 TiO3- x mol% K 0.5 Bi 0.5 TiO3- y mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 O3- z wt% MeF2, 18<x<22.9, 5.9<y<9.5, 4.6<z<6.7, Me=Ca, Sr, Ba, any one of these proportions is weighed and mixed in a ball mill jar. Zirconia balls and deionized water are added as the ball milling media, and the mixture is ball milled. After ball milling, the material is discharged and dried.
[0011] 2) Pour the dried powder from step 1) into a mortar and grind it, then pre-calcine it at a high temperature;
[0012] 3) The powder after high-temperature pre-firing is ground and then put into a ball mill jar with deionized water for secondary ball milling. The slurry after secondary ball milling is discharged, dried, and ceramic powder is obtained.
[0013] 4) The dried ceramic powder from step 3) is loaded into the mold, pre-pressed, and then rapidly sintered in a spark plasma sintering furnace. After sintering, the mold is removed, thus obtaining a lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability prepared by rapid sintering technology.
[0014] In step 1), the purity of all raw materials, including titanium dioxide, bismuth trioxide, anhydrous potassium carbonate, anhydrous sodium carbonate, tin dioxide, zirconium dioxide, calcium carbonate, strontium carbonate, calcium fluoride, strontium fluoride, and barium fluoride, is 99.90-99.99%.
[0015] In step 1), the particle size of all raw materials, including titanium dioxide, bismuth trioxide, anhydrous potassium carbonate, anhydrous sodium carbonate, tin dioxide, zirconium dioxide, calcium carbonate, strontium carbonate, calcium fluoride, strontium fluoride, and barium fluoride, is 0.8-1 μm.
[0016] In step 1), ball milling is performed at a speed of 330-360 rpm for 28-29 hours.
[0017] In step 1), the amount of zirconium dioxide balls added accounts for 1 / 4 to 1 / 2 of the volume of the ball mill jar.
[0018] In step 1), the amount of deionized water added accounts for 1 / 6 to 1 / 4 of the volume of the ball mill jar;
[0019] The drying described in step 1) is carried out in an oven at a temperature of 80-90℃ for 36-40 hours.
[0020] The grinding time in step 2) is 20-40 min; after ball milling, the powder will have unevenness due to the different settling rates of the slurry during the drying process. Therefore, grinding is necessary to help make the powder composition uniform.
[0021] The high-temperature pre-firing mentioned in step 2) is carried out in an alumina crucible; the pre-firing temperature is 835~855℃, the holding time is 5.5~6.5 h; the atmosphere is air; the purpose of pre-firing is to form a phase in advance.
[0022] In step 3), the powder that has been pre-fired at high temperature is placed in an agate mortar and ground for 20-40 minutes to prevent uneven material composition during the pre-firing process.
[0023] In step 3), deionized water and zirconia balls are added to the ball mill jar for a second ball milling. The amount of deionized water added accounts for 1 / 6 to 1 / 4 of the volume of the ball mill jar; the amount of zirconia balls added accounts for 1 / 4 to 1 / 2 of the volume of the ball mill jar.
[0024] In step 3), the secondary ball milling is performed at a speed of 350-400 rpm for 28-29 hours.
[0025] In step 3), the drying process is carried out at a temperature of 130-140℃ for 18-20 hours.
[0026] In step 4), the dried ceramic powder from step 3) is loaded into the mold. Specifically, the dried ceramic powder from step 3) is loaded into the graphite mold, and the powder is separated from the mold with graphite paper. Boron nitride solution is then applied around the mold.
[0027] In step 4), the diameter of the graphite mold is 9.5-10.5 mm;
[0028] In step 4), the concentration of the boron nitride solution applied is 0.5-1 mg / ml;
[0029] In step 4), the pre-compression process uses a pre-compression molding pressure of 4-6 MPa and a time of 5-8 min.
[0030] In step 4), the rapid sintering uses a vacuum pressure of 25-35 MPa and a heating rate of 80-110℃ / min for spark plasma sintering; the sintering temperature is 875-1000℃ and the holding time is 3-8 min.
[0031] This invention provides an application of a lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability, prepared by rapid sintering technology, for use in ceramic energy storage capacitors, which combines excellent dielectric temperature stability and energy storage characteristics.
[0032] Compared with existing technologies, the preparation process of this invention is simple. By introducing fluorides to increase the relaxation degree of the material, its microstructure is optimized, ultimately achieving a synergistic regulatory effect and significantly improving the energy storage characteristics of lead-free sodium bismuth titanate-based ceramic materials. Furthermore, this invention enables high-throughput preparation, greatly saving labor costs, and offers good repeatability, high reliability, and inexpensive raw materials that are environmentally and human-friendly. The obtained bulk ceramic capacitor material possesses both excellent dielectric temperature stability and energy storage characteristics, showing promising prospects for industrialization. Attached Figure Description
[0033] Figure 1 The 74 mol% Na obtained in the embodiments of the present invention 0.5 Bi 0.5 TiO3- 20 mol% K 0.5 Bi 0.5 TiO3- 6mol% Sr 0.25 Ca 0.25 Na 0.25Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 X-ray spectra of O3- 5 wt% CaF2 ceramic bulk material;
[0034] Figure 2 The 74 mol% Na obtained in the embodiments of the present invention 0.5 Bi 0.5 TiO3- 20 mol% K 0.5 Bi 0.5 TiO3- 6mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 Microscopic morphology photograph of O3- 5 wt% CaF2 ceramic bulk material;
[0035] Figure 3 The 74 mol% Na obtained in the embodiments of the present invention 0.5 Bi 0.5 TiO3- 20 mol% K 0.5 Bi 0.5 TiO3- 6mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 The dielectric constant and loss of O3- 5 wt% CaF2 ceramic bulk material under different frequency conditions vary with temperature.
[0036] Figure 4 The 74 mol% Na obtained in the embodiments of the present invention is shown below. 0.5 Bi 0.5 TiO3- 20mol% K 0.5 Bi 0.5 TiO3- 6 mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 The graph shows the rate of change of dielectric constant of O3- 5 wt% CaF2 ceramic bulk material under different frequency conditions as a function of temperature.
[0037] Figure 5The 74 mol% Na obtained in the embodiments of the present invention 0.5 Bi 0.5 TiO3- 20 mol% K 0.5 Bi 0.5 TiO3- 6mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 Pivot distribution fitting plot of O3- 5 wt% CaF2 ceramic bulk material;
[0038] Figure 6 The 74 mol% Na obtained in the embodiments of the present invention 0.5 Bi 0.5 TiO3- 20 mol% K 0.5 Bi 0.5 TiO3- 6mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 Hysteresis loop of O3- 5 wt% CaF2 ceramic bulk material at room temperature;
[0039] Figure 7 The 74 mol% Na obtained in the embodiments of the present invention 0.5 Bi 0.5 TiO3- 20 mol% K 0.5 Bi 0.5 TiO3- 6mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 Hysteresis loop diagram of O3- 5 wt% CaF2 ceramic bulk material under varying temperatures;
[0040] Figure 8 The 74 mol% Na obtained in the embodiments of the present invention 0.5 Bi 0.5 TiO3- 20 mol% K 0.5 Bi 0.5 TiO3- 6mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti0.69 Zr 0.14 Sn 0.17 Frequency conversion hysteresis loop diagram of O3- 5 wt% CaF2 ceramic bulk material;
[0041] Figure 9 The 74 mol% Na obtained in the embodiments of the present invention 0.5 Bi 0.5 TiO3- 20 mol% K 0.5 Bi 0.5 TiO3- 6mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 Current curve of O3- 5 wt% CaF2 ceramic bulk material under underdamped state;
[0042] Figure 10 The 74 mol% Na obtained in the embodiments of the present invention 0.5 Bi 0.5 TiO3- 20 mol% K 0.5 Bi 0.5 TiO3- 6mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 Current curves of O3- 5 wt% CaF2 ceramic bulk material under overdamped state. Detailed Implementation
[0043] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0044] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.
[0045] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.
[0046] Example 1
[0047] A method for preparing a lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability using a rapid sintering technique includes the following steps:
[0048] 1) Titanium dioxide, bismuth trioxide, anhydrous potassium carbonate, anhydrous sodium carbonate, tin dioxide, zirconium dioxide, calcium carbonate, strontium carbonate, and calcium fluoride raw materials with a purity of 99.95% were mixed in a stoichiometric ratio of 74 mol% Na. 0.5 Bi 0.5 TiO3- 20 mol%K 0.5 Bi 0.5 TiO3- 6 mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 O3-5 wt% CaF2 powder was placed in a 250 mL nylon ball mill jar. High-quality zirconia balls and deionized water were selected as the milling media. The amount of zirconia balls added was 1 / 3 of the volume of the ball mill jar, and the amount of deionized water added was 1 / 5 of the volume of the ball mill jar. The mixing and milling time was 29 h, and the rotation speed was 340 rpm. The product obtained after ball milling was dried in an oven at 85℃ for 38 h.
[0049] 2) Take out the dried powder and grind it thoroughly for 30 min. Then put it into a high-temperature alumina crucible and pre-calcine it at 845 °C in air atmosphere for 6 h under sealed conditions.
[0050] 3) The pre-fired powder is then placed in an agate mortar and ground for 30 minutes. It is then placed in a nylon ball mill jar, and deionized water is added to fill 1 / 5 of the jar volume. Zirconia balls are added to fill 1 / 3 of the jar volume for a second ball milling. The ball milling time is 28 hours and the rotation speed is 350 rpm. The slurry obtained after ball milling is dried at 135℃ for 19 hours to obtain the corresponding ceramic powder.
[0051] 4) The obtained ceramic powder was loaded into a graphite mold with a diameter of 10 mm, and the powder was separated from the mold with graphite paper. A boron nitride solution with a concentration of 0.8 mg / ml was applied around the mold. The powder was pre-pressed under a pressure of 5 MPa for 7 min, and then rapidly sintered in a spark plasma sintering furnace at a sintering temperature of 900℃, a holding time of 5 min, a vacuum pressure of 30 MPa, and a heating rate of 90℃ / min. After sintering, the powder was demolded to obtain the sodium bismuth titanate-based environmentally friendly composite ceramic material.
[0052] The lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic prepared in Example 1 was characterized in terms of its phase structure and microstructure, such as... Figure 1 、 Figure 2 As shown, the ceramic material obtained by the above preparation method has a phase composition of sodium bismuth titanate as the main phase and contains a small amount of CaF2 as the second phase, and has a dense microstructure. As is well known, a small grain size and a dense microstructure are prerequisites for its excellent energy storage properties. Figure 2 The SEM images show a dense microstructure and fine grains, indicating that the microstructure has been optimized.
[0053] By testing the dielectric constant and loss of the sample under different frequency and temperature conditions, such as... Figure 3 As shown, this bismuth sodium titanate-based environmentally friendly composite ceramic material maintains a dielectric constant of around 800 under conditions of 1 kHz-1 MHz, while also possessing a low dielectric loss value. The relaxation degree of the material is increased by introducing fluorides. Furthermore, within a temperature range of -61℃ to 300℃, the rate of change of the dielectric constant at multiple frequencies is within ±15%, such as... Figure 4 As shown. It is obvious that the bismuth sodium titanate-based environmentally friendly composite ceramic materials of the present invention all have high temperature stability and meet the industry standard of X9R ceramic capacitors (-15% ≤ capacitance change rate ≤ 15%).
[0054] Through multiple electrical breakdown tests, and by using the Weber distribution to determine its reliable breakdown field strength (440 kV / cm), such as... Figure 5 As shown. Based on the experimental results obtained above, the PE curve was tested under this electric field strength, as shown. Figure 6 As shown, this sodium bismuth titanate-based environmentally friendly composite ceramic material can achieve a relatively high effective energy storage density of ~7.1 J / cm under an electric field strength of 440 kV / cm. 3 And maintain a moderate energy storage efficiency value, such as 76%.
[0055] Furthermore, the sample also exhibits excellent energy storage stability within a temperature range of 20℃ to 120℃, such as... Figure 7 As shown. Furthermore, within the frequency range of 1 Hz to 1000 Hz, this sample also exhibits excellent energy storage characteristics, such as... Figure 8 As shown in the image. Furthermore, this sample also possesses a high power density, such as 24.2 MW / cm². 3 With extremely fast charge and discharge speeds, such as 85 ns, such as Figure 9 and Figure 10 As shown, this meets the practical application requirements of ceramic energy storage capacitors and is expected to be used in the electronic ceramics market.
[0056] The lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic prepared by this invention has excellent energy storage characteristics (effective energy storage density of 7.1 J / cm³). 3 Furthermore, its excellent dielectric temperature stability meets the requirements for use in X9R capacitors, and it has broad application prospects in fields such as electromagnetic catapults and new energy vehicles.
[0057] The above description of the embodiments is intended to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability, prepared by rapid sintering technology, characterized in that... The lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic is (100- xy ) mol%Na 0.5 Bi 0.5 TiO3- x mol% K 0.5 Bi 0.5 TiO3- y mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 O3- z wt% MeF2, 18 < x < 22.9, 5.9 < y < 9.5, 4.6 < z < 6.7, Me = any one of Ca, Sr, or Ba; The lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic prepared by the rapid sintering technology exhibits excellent dielectric temperature stability, with a dielectric constant change rate within ±15% at 1kHz, 10kHz, 100kHz, and 1MHz within a temperature range of -61℃ to 300℃.
2. A method for preparing a lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability prepared by the rapid sintering technology described in claim 1, characterized in that, The preparation method includes the following steps: 1) Using any one of the following as starting materials: titanium dioxide, bismuth trioxide, anhydrous potassium carbonate, anhydrous sodium carbonate, tin dioxide, zirconium dioxide, calcium carbonate, strontium carbonate, calcium fluoride, strontium fluoride, and barium fluoride, according to (100-xy) mol% Na 0.5 Bi 0.5 TiO3- x mol% K 0.5 Bi 0.5 TiO3- y mol% Sr 0.25 Ca 0.25 Na 0.25 Bi 0.25 Ti 0.69 Zr 0.14 Sn 0.17 O3-z wt% MeF2, 18<x<22.9, 5.9<y<9.5, 4.6<z<6.7, Me=Ca, Sr, Ba, any one of these proportions is weighed and mixed in a ball mill jar. Zirconia balls and deionized water are added as the ball milling media for ball milling. After ball milling, the material is discharged and dried. 2) Pour the dried powder from step 1) into a mortar and grind it, then pre-calcine it at a high temperature; 3) The powder after high-temperature pre-firing is ground and then put into a ball mill jar with deionized water for secondary ball milling. The slurry after secondary ball milling is discharged, dried, and ceramic powder is obtained. 4) The dried ceramic powder from step 3) is loaded into the mold, pre-pressed, and then rapidly sintered in a spark plasma sintering furnace. After sintering, the mold is removed, thus obtaining a lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability prepared by rapid sintering technology.
3. The preparation method according to claim 2, characterized in that, In step 1), ball milling is performed at a speed of 330-360 rpm for 28-29 hours.
4. The preparation method according to claim 2 or 3, characterized in that, The high-temperature pre-firing mentioned in step 2) is carried out in an alumina crucible; the pre-firing temperature is 835~855℃ and the holding time is 5.5~6.5 h.
5. The preparation method according to claim 2, characterized in that, In step 3), the secondary ball milling is performed at a speed of 350-400 rpm for 28-29 hours.
6. The preparation method according to claim 2 or 5, characterized in that, In step 3), the drying process is carried out at a temperature of 130-140℃ for 18-20 hours.
7. The preparation method according to claim 2, characterized in that, In step 4), the pre-compression process uses a pressure of 4-6 MPa and a time of 5-8 min.
8. The preparation method according to claim 2, characterized in that, In step 4), the rapid sintering uses a vacuum pressure of 25-35 MPa and a heating rate of 80-110℃ / min for spark plasma sintering; the sintering temperature is 875-1000℃ and the holding time is 3-8 min.
9. An application of a lead-free, environmentally friendly sodium bismuth titanate-based composite dielectric energy storage ceramic with excellent dielectric temperature stability prepared by the rapid sintering technology described in claim 1, characterized in that, Used in ceramic energy storage capacitors.
Citation Information
Patent Citations
Unleaded ceramic with high voltage and high energy density simultaneously and preparation method for unleaded ceramic
CN104710174A
High-energy-density barium sodium niobate-based glass ceramic energy storage material as well as preparation and application thereof
CN109467313A
High-energy-storage-density sodium bismuth titanate-based lead-free dielectric material and preparation method thereof
CN112341192A